Complex influences of mechanistic knowledge, worldview, and quantitative reasoning on climate change discourse: Evidence for ideologically motivated reasoning among youth. Issue 1 (28th July 2020) - Zummo, Lynne; Donovan, Brian; Busch, K. C.
Abstract: Anthropogenic climate change remains divisive in the United States, where skepticism of the scientific consensus is associated with conservative worldviews, resulting in political polarization. This study considers three hypotheses regarding U.S. polarization over climate change that have emerged from social psychology research and applies them to science education by showing how these hypotheses could relate to adolescents' science learning. We then test each hypothesis within an experimental educational intervention designed to study the influence of worldview, mechanistic knowledge, and quantitative reasoning on students' written arguments about climate change. We used mixed methods to analyze the results of this individually randomized trial with clustering involving 357 participants in grades 9–11 from 5 U.S. sites. Findings show that: (a) exposure to mechanistic knowledge about climate change increased odds of receptivity toward climate change; (b) increasingly conservative worldviews were associated with decreased odds of receptivity; (c) worldview and quantitative reasoning interacted, resulting in an amplified effect of worldview for students with greater quantitative reasoning. Results also suggest that the influence of worldview and mechanistic knowledge on receptivity work independently from one another in our dataset. This study demonstrates the value of teaching mechanistic understandings of climate change, yet also demonstrates the influence of worldview on receptivity to climate change for adolescents, as well as complex interactions between quantitative reasoning (something school science aims to develop) and worldview. It shows that moving the U.S. public toward the scientific consensus is complex and involves confronting ideologically motivated reasoning within science education.